Enlarged rete pegs with excessive accumulation of melanosomes leading to darker aging spots revealed by histomorphological measurements of internal structures of the epidermis - Yamamura, Tatsuo; Kobayashi, Soko; Yoshida, Ikuyo; Kuriyama, Ken‐ichi (International journal of cosmetic science, 2023)
Objective Various histological studies of facial pigmented spot sites such as solar lentigo have been reported, but few studies have used quantitative indices by histomorphometric analysis of the internal structure of pigmented spot sites using non‐invasive methods. In the present study, to quantitatively elucidate morphological changes in the epidermis in male, darker‐pigmented spots and female, light‐pigmented spots, indices that characterize the internal structure of the epidermis in pigmented spot sites were measured using in vivo confocal laser scanning microscopy (CLSM). Methods The darkness of pigmented spots on the cheeks of 69 women and 43 men was analysed using image analysis software. The L* value was calculated from RGB values obtained from facial images. The internal structures of pigmented spots on the cheeks of 13 subjects were observed by CLSM. Various parameters were measured using CLSM images from the surface of the stratum corneum to the bottom of the dermal papillae, including the thickness of the epidermis, melanosome content, and shape of the dermal papillae. Results Mean ΔL* values between pigmented spots and non‐pigmented areas of male subjects were significantly increased in the 40s and 50s compared with those of female subjects. Conspicuous pigmented spots increased in the 40s in male subjects and the 50s in female subjects. In CLSM observations, significant increases in the thickness of the epidermis and melanosome content were confirmed in pigmented spots compared with surrounding non‐pigmented areas. In particular, melanosome content in the male subject group with dark‐coloured pigmented spots increased significantly to about eight times that of non‐pigmented areas, and more than double that of the male subject group with light‐coloured pigmented spots. Conclusion From the measurements of quantitative parameters, morphological changes in the epidermis were clearly related to the surface colour tone of pigmented spots. Darker pigmented spot sites tended to show longer rete pegs in the epidermis. Accumulation of melanosomes in epidermal basal cells could be considered to increase with the degree of elongation of rete pegs at pigmented spot sites and, thus, induce darker pigmented spots. Résumé Objectif Même si diverses études histologiques des taches pigmentées du visage, tels que les lentigos solaires, ont été publiées, il n'existe que peu d'études ayant utilisé des indices quantitatifs par analyse histomorphométrique de la structure interne des taches pigmentées via des méthodes non invasives. Dans la présente étude, afin d'expliquer quantitativement les changements morphologiques dans l'épiderme des taches pigmentées plus foncées chez l'homme et des taches pigmentées légères chez la femme, les indices qui caractérisent la structure interne de l'épiderme dans les taches pigmentées ont été mesurés par microscopie confocale à balayage laser (MCBL) in vivo. Méthodes L'aspect foncé des taches pigmentées sur les joues de 69 femmes et 43 hommes a été analysé à l'aide d'un logiciel d'analyse d'images. La valeur L* a été calculée à partir des valeurs RVB obtenues des images du visage. Sur les joues de 13 sujets, les structures internes des taches pigmentées ont été observées par MCBL. Divers paramètres ont été mesurés à l'aide des images provenant de la MCBL, de la surface de la couche cornée jusqu'au bas des papilles dermiques, y compris l'épaisseur de l'épiderme, la teneur en mélanosome et la forme des papilles dermiques. Résultats Les valeurs moyennes de ΔL* entre les zones de taches pigmentées et non pigmentées des hommes ont augmenté de manière significative chez les sujets dans la quarantaine et la cinquantaine par rapport aux valeurs des femmes. Chez les hommes, les taches pigmentées visibles ont augmenté dans la quarantaine, tandis qu'elles ont augmenté dans la cinquantaine chez les femmes. Dans les observations par MCBL, des augmentations significatives de l'épaisseur de l'épiderme et de la teneur en mélanosome ont été confirmées dans les zones de taches pigmentées par rapport aux zones de taches non pigmentées environnantes. Dans le groupe d'hommes présentant des taches pigmentées de couleur foncée en particulier, la teneur en mélanosomes a augmenté de façon significative jusqu'à environ 8 fois celle des zones non pigmentées, et jusqu'à plus du double de celle du groupe d'hommes présentant des taches pigmentées de couleur claire. Conclusion D'après les mesures des paramètres quantitatifs, les changements morphologiques dans l'épiderme étaient clairement liés à la couleur à la surface des taches pigmentées. Les sites de taches pigmentées plus foncées montraient généralement des extensions des crêtes épidermiques dans l'épiderme. On pourrait envisager que l'accumulation de mélanosomes dans les cellules basales épidermiques augmente selon le degré d'allongement des crêtes épidermiques au niveau des sites de taches pigmentées, et entraîne ainsi des taches pigmentées plus foncées. Three‐dimensional stereoscopic images of rete pegs in dark‐colored pigmented spots from males and females constructed from stack images of horizontal sections after the binarization processes. Multiple rete pegs are intertwined to form a large and intricate complex structure in dark‐colored pigmented spots from male subjects. The rete pegs in dark‐colored pigmented spots from female subjects are elongated smoothly and independently.